Physician burnout in ophthalmology: U.S. survey. Issue 6 (June 2022) - Sedhom, Jessica A.; Patnaik, Jennifer L.; McCourt, Emily A.; Liao, Sophie; Subramanian, Prem S.; Davidson, Richard S.; Palestine, Alan G.; Kahook, Malik Y.; Seibold, Leonard K.
Abstract : In this cross-sectional study of ophthalmologists in the United States, 37.8% self-reported symptoms of occupational burnout. Among those surveyed, sex, practice type, and employment autonomy were the highest risk factors. Abstract : Purpose: To determine the prevalence of physician burnout among ophthalmologists in the United States and identify associated risks. Setting: All practice types within the United States. Design: Cross-sectional study. Methods: A survey was distributed through email listservs to several national ophthalmology societies. Participants completed a modified Mini Z Burnout Survey, a 10-item questionnaire measured in 5-point Likert scales, followed by demographic questions. The Mini Z Burnout survey assessed 3 main outcomes: stress, burnout, and work satisfaction. The percentage of subgroups experiencing burnout were presented and comparisons made with odds ratios from logistic regression modeling. Results: Of the 592 ophthalmologists responding to the survey, 37.8% (224) self-reported symptoms of burnout with a low of 30.8% (12/39) for vitreoretinal specialists to a high of 45.4% (30/66) for uveitis specialists. Most of those reporting burnout were categorized as mild (65.2% [146/224]), followed by moderate (29.5% [66/224]) and severe (5.4% [12/224]). Women had almost twice the odds of reporting burnout (odds ratio [OR] = 1.9 [95% CI: 1.3-2.7]; P = .0005). Physicians employed in academic (OR = 2.0 [95% CI: 1.2-3.2]; P = 0.007) and hospital facilities (OR = 2.4 [95% CI: 1.3-4.6]; P = .008) reported higher rates of burnout compared with those in large private groups. Burnout was associated with self-reported low work control, insufficient time for documentation, and misalignment with departmental leaders ( P < .0001). Conclusions: Ophthalmologists exhibited a high degree of self-reported burnout in the U.S. This study highlights sex, employment autonomy, and practice type as major factors associated with burnout.